A novel alcohol steamed preparation from Gastrodia elata Blume: Pharmacological assessment of a functional food - Cheng, Lijun; Wang, Hui; Ma, Kejian; Deng, Yang; Li, Maoru; Ma, Ji (Frontiers in Pharmacology, 2023)
Gastrodia elata Blume (GE) is traditionally used as medicinal and functional food, which was proved to be effective on mental disorder. GE was usually washed, steamed by water, dried and sliced in traditional processing technology. In this study, a novel processing technology-alcohol steamed GE (AGE) was proposed. Compared with fresh GE, the relative content of parishin A and parishin E decreased after alcohol steaming, whereas gastrodin (GAS), p-hydroxylbenzyl alcohol (HBA), Parishin B and Parishin C were increased. Additionally, pentobarbital-induced sleep mice model and Chronic Restraint Stress (CRS) model were applied to evaluate the pharmacological efficacy of fresh GE and steamed GE, and both fresh and steamed GE showed an intensive hypnotic and anti-anxiety effect. Furthermore, the anti-anxiety mechanism based on serum metabolic was investigated and the tryptophan metabolic pathway was considered the response to the anti-anxiety effect of GE. Although the optimization of the processing technology of AGE still needs to be further explored, the current results have provided new thoughts for the processing technology and clinical application of GE.